2017
DOI: 10.1016/j.joca.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation modulus of murine cartilage: a sensitive indicator of the initiation and progression of post-traumatic osteoarthritis

Abstract: Objective This study aims to demonstrate that cartilage nanoindentation modulus is a highly sensitive indicator of the onset and spatiotemporal progression of post-traumatic osteoarthritis (PTOA) in murine models. Design Destabilization of medial meniscus (DMM) surgery was performed on the right knees of 12-week old male, wild-type C57BL/6 mice, with Sham control on contralateral left knees. Atomic force microscopy (AFM)-based nanoindentation was applied to quantify the nanoindentation modulus, Eind, of femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 49 publications
9
90
1
Order By: Relevance
“…5B). These data also match our current observation that DMM surgery rapidly reduced surface E ind of WT mouse cartilage (16). Taken together, our results clearly demonstrate that EGFR signaling regulates mechanical properties of articular cartilage.…”
Section: Egfr Signaling Promotes the Lubrication Function Of Articularsupporting
confidence: 92%
See 1 more Smart Citation
“…5B). These data also match our current observation that DMM surgery rapidly reduced surface E ind of WT mouse cartilage (16). Taken together, our results clearly demonstrate that EGFR signaling regulates mechanical properties of articular cartilage.…”
Section: Egfr Signaling Promotes the Lubrication Function Of Articularsupporting
confidence: 92%
“…7D). As OA further develops, the DMM site of WT mice also exhibited the same or elevated E ind compared with the sham site (16). Fourth, pain is the major symptom in OA.…”
Section: Loss Of Egfr In Chondrocytes Remarkably Accelerates Cartilagementioning
confidence: 90%
“…Yet it is likely that these behaviors vary with the underlying chemistry and extracellular matrix organization in zonal cartilage. Indentation of the articular surface has evaluated equilibrium properties of native, diseased, and repair cartilage [2428] and begun to explore the time-dependent response [9,22,29,30]. Results were combined with finite element models [21,31] and correlated with chemistry in maps spanning osteochondral tissues [3234].…”
Section: Introductionmentioning
confidence: 99%
“…Micro‐sized tips showed no change in stiffness until much later stages of degeneration, at which point compliance decreased. Han et al showed that a decrease in surface stiffness could be observed as early as one week after injury in a small animal model of post‐traumatic osteoarthritis . While most AFM approaches rely on simple elastic indentation tests, Grodzinsky et al used microrheology in conjunction with a poroelastic model to determine parameters like the Young's modulus of the fibrillary and non‐fibrillary components and the hydraulic permeability .…”
Section: Physical Probing Of Chondrocytes and Their Peri‐ And Extra‐cmentioning
confidence: 99%
“…Han et al showed that a decrease in surface stiffness could be observed as early as one week after injury in a small animal model of post-traumatic osteoarthritis. 67 While most AFM approaches rely on simple elastic indentation tests, Grodzinsky et al used microrheology in conjunction with a poroelastic model to determine parameters like the Young's modulus of the fibrillary and non-fibrillary components and the hydraulic permeability. 68 With this type of approach, increased fluid flow in in the tissue was noted as an early and sensitive microscale marker of cartilage degradation.…”
Section: Microscale Mechanical Properties Of Cartilage Matrixmentioning
confidence: 99%